2014
DOI: 10.5772/58564
|View full text |Cite
|
Sign up to set email alerts
|

CPG-based Locomotion Controller Design for a Boxfish-like Robot

Abstract: This paper focuses on a Central Pattern Generator (CPG)-based locomotion controller design for a boxfish-like robot. The bio-inspired controller is aimed at flexible switching in multiple 3D swimming patterns and exact attitude control of yaw and roll such that the robot will swim more like a real boxfish. The CPG network comprises two layers, the lower layer is the network of coupled linear oscillators and the upper is the transition layer where the lower-dimensional locomotion stimuli are transformed into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…1 Among underwater robots, swimming robots have significant potential for study of marine life, monitoring oceanic environments, and underwater operations. [2][3][4][5][6][7] As a specific sea creature, jellyfish has a soft body, which is found in the waters all over the world. Owing to low metabolic rate, jellyfish has the ability to move vertically without expending much energy, while it passively depends on ocean current, tides, and wind for horizontal movements.…”
Section: Introductionmentioning
confidence: 99%
“…1 Among underwater robots, swimming robots have significant potential for study of marine life, monitoring oceanic environments, and underwater operations. [2][3][4][5][6][7] As a specific sea creature, jellyfish has a soft body, which is found in the waters all over the world. Owing to low metabolic rate, jellyfish has the ability to move vertically without expending much energy, while it passively depends on ocean current, tides, and wind for horizontal movements.…”
Section: Introductionmentioning
confidence: 99%
“…However, the merits of the caudal fins had not been explored for the driving limitation of IPMC. There have also been many developed fish-like prototypes with dual pectoral fins, including the MPF-like robotic fishes [7][8][9] and BCF-like robotic fishes [12,40,41]. In the MPF-like robotic fishes, the long base of dual pectoral fins usually requires more DoFs, which increases the complexity of the structure.…”
Section: Discussionmentioning
confidence: 99%
“…The robot is controlled by an artificial CPG network whose stability has been strictly proved in our previous paper [24]. The linear CPG model takes the forṁ…”
Section: The Robotic Fish Prototypementioning
confidence: 99%
“…In our previous work, we have developed a boxfish-like robot to study fishlike locomotion [24]. Hydrodynamic simulations and on-site experiments with the robot have demonstrated that our robot can always mimic the freely swimming locomotion of its biological counterpart [13].…”
Section: Introductionmentioning
confidence: 99%